Molecular Characteristics and Genetic Evolution of Echovirus 33 in Mainland of China - Wenhui Wang; Huan Fan; Shuaifeng Zhou; Shikang Li; Alitengsaier NIGEDELI; Yong Zhang; Qiang Sun; Yun He; Qin Guo; Xiaoyi Wang; Huanhuan Lu; Jinbo Xiao; et al. (Pathogens, 2022)
Echovirus, a member of the Enterovirus B (EV-B) family, has led to numerous outbreaks and pandemics, causing a broad spectrum of diseases. Based on the national hand, foot, and mouth disease (HFMD) surveillance system, seven strains of echovirus 33 (E33) were isolated from Mainland of China between 2010 and 2018. The whole genomes of these strains were isolated and sequenced, and phylogenetic trees were constructed based on the gene sequences in different regions of the EV-B prototype strains. It was found that E33 may be recombined in the P2 and P3 regions. Five genotypes (A–E) were defined based on the entire VP1 region of E33, of which the C gene subtype was the dominant gene subtype at present. Recombinant analysis showed that genotype C strains likely recombined with EV-B80, EV-B85, E13, and CVA9 in the P2 and P3 regions, while genotype E had the possibility of recombination with CVB3, E3, E6, and E4. Results of Bayesian analysis indicated that E33 may have appeared around 1955 (95% confidence interval: 1945–1959), with a high evolutionary rate of 1.11 × 10−2 substitution/site/year (95% highest posterior density (HPD): 8.17 × 10−3 to 1.4 × 10−2 substitution/site/year). According to spatial transmission route analysis, two significant transmission routes were identified: from Australia to India and from Oman to Thailand, which the E33 strain in Mainland of China likely introduced from Mexico and India. In conclusion, our study fills the gaps in the evolutionary analysis of E33 and can provide important data for enterovirus surveillance.